The EUTOS long-term survival (ELTS) score is superior to the Sokal score for predicting survival in chronic myeloid leukemia - Pfirrmann, Markus; Clark, Richard E; Prejzner, Witold; Lauseker, Michael; Baccarani, Michele; Saussele, Susanne; Guilhot, François; Heibl, Sonja; Hehlmann, Rüdiger; Faber, Edgar; Turkina, Anna; Ossenkoppele, Gert; et al. (Leukemia, 2020)
Prognostic scores support clinicians in selecting risk-adjusted treatments and in comparatively assessing different results. For patients with chronic-phase chronic myeloid leukemia (CML), four baseline prognostic scores are commonly used. Our aim was to compare the prognostic performance of the scores and to arrive at an evidence-based score recommendation. In 2949 patients not involved in any score development, higher hazard ratios and concordance indices in any comparison demonstrated the best discrimination of long-term survival with the ELTS score. In a second step, of 5154 patients analyzed to investigate risk group classification differences, 23% (n = 1197) were allocated to high-risk by the Sokal score. Of the 1197 Sokal high-risk patients, 56% were non-high-risk according to the ELTS score and had a significantly more favorable long-term survival prognosis than the 526 high-risk patients according to both scores. The Sokal score identified too many patients as high-risk and relatively few (40%) as low-risk (versus 60% with the ELTS score). Inappropriate risk classification jeopardizes optimal treatment selection. The ELTS score outperformed the Sokal score, the Euro, and the EUTOS score regarding risk group discrimination. The recent recommendation of the European LeukemiaNet for preferred use of the ELTS score was supported with significant statistical evidence.
Keywords: dospělí; Female; inhibitory proteinkinas; Adult; mladý dospělý; ženské pohlaví; Adolescent; Registries; lidé; chronická myeloidní leukemie; Probability; Aged, 80 and over; prognóza; pravděpodobnost; Male; Protein Kinase Inhibitors; Aged; Young Adult; Prognosis; lidé středního věku; registrace; senioři nad 80 let; senioři; mužské pohlaví; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Middle Aged; mladiství; Humans